The First Application of The Electrodynamic Wagon Retarder in Poland - Jerzy Mikulski; Jakub Mlynczak (Communications - Scientific letters of the University of Zilina, 2011)
The article discusses design and installation method of the EDG Electrodynamic Wagon Retarder at the railway siding of the Power Plant Rybnik. It is the first structure of its kind in Poland. Up to now mostly hydraulic brakes have been used in Poland. They were difficult to operate and hardly environmentally friendly due to contamination and noise. Electrodynamic wagon retarders are free from such defects. The issue of introducing new railroad brake construction in Poland is very important because the Polish Railway Lines (PLK) are confronted with the need of devices modernization on a humps. The German railways’ experience confirms the effectiveness of this type of brake. Especially the field tests in Germany and Poland show that the electrodynamic retarders do not have a negative impact on the occupancy control system.